Learning Desain Based on Schoology and Zoom Meeting - Dilla Octavianingrum (Universitas Muhammadiyah Mataram, 2021)
The purpose of this study is to describe the design of learning based on Schoology and Zoom Meeting. In the final stage, the effectiveness of using e-learning will be known.Learning during the COVID-19 pandemic makes students less motivated to study. Most students choose to do face-to-face learning compared to online. These problems certainly make lecturers have to think creatively in delivering teaching materials to their students. The learning design by mixing and matching the Schoology and Zoom Meeting platforms is one of the innovations of learning media in the COVID-19 pandemic situation. The design of learning media is carried out in the lesson planning course, because it is one of the courses that must be mastered by prospective students of Cultural Arts teachers. This design is expected to make students focus on receiving teaching materials so they can apply them in future work. The results of this study are able to describe the learning design of the Learning Planning subject based on e-learning Scchoology and Zoom Meeting.